2010
DOI: 10.1007/s10529-010-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of recombinant E. coli expressing cyclopentanone monooxygenase in polyelectrolyte complex capsules for Baeyer–Villiger biooxidation of 8-oxabicyclo[3.2.1]oct-6-en-3-one

Abstract: Recombinant Escherichia coli cells, over-expressing cyclopentanone monooxygenase activity, were immobilized in polyelectrolyte complex capsules, made of sodium alginate, cellulose sulfate, poly(methylene-co-guanidine), CaCl(2) and NaCl. More than 90% of the cell viability was preserved during the encapsulation process. Moreover, the initial enzyme activity was fully maintained within encapsulated cells while it halved in free cells. Both encapsulated and free cells reached the end point of the Baeyer-Villiger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
(25 reference statements)
2
22
0
Order By: Relevance
“…The first study deals with the immobilization of microorganism in polyeletrolyte complexes. 80 Microorganisms usually have a negatively charged surface, and are regarded as enzyme clusters, so that the immobilized cell can be used as a micro-scale plant. In this study, it was found that almost all (90%) of the immobilized recombinant Escherichia coli cells were viable, and the enzymes in the cells maintained their initial activity.…”
Section: ·5 Other Properties and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study deals with the immobilization of microorganism in polyeletrolyte complexes. 80 Microorganisms usually have a negatively charged surface, and are regarded as enzyme clusters, so that the immobilized cell can be used as a micro-scale plant. In this study, it was found that almost all (90%) of the immobilized recombinant Escherichia coli cells were viable, and the enzymes in the cells maintained their initial activity.…”
Section: ·5 Other Properties and Applicationsmentioning
confidence: 99%
“…In this study, it was found that almost all (90%) of the immobilized recombinant Escherichia coli cells were viable, and the enzymes in the cells maintained their initial activity. 80 The second study deals with a gold nanoparticle immobilized PIC membrane. Antibodies were immobilized on gold nanoparticles and the antibodies were used for electrochemical immunosensing.…”
Section: ·5 Other Properties and Applicationsmentioning
confidence: 99%
“…One of the validated techniques for immobilizing viable recombinant cells is their encapsulation in polyelectrolyte complex (PEC) capsules, which afforded promising results in the previous development of encapsulated viable whole-cell biocatalysts [3][4][5]. PEC capsules have been produced by a single-step polyelectrolyte complexation of oppositely-charged polyanion (PA) aqueous solutions consisting of cellulose sulphate (CS), high-viscosity sodium alginate and living bacterial cells with a polycation solution of poly(methylene-co-guanidine) (PMCG), CaCl 2 as gelling and NaCl as antigelling agents [6].…”
Section: Introductionmentioning
confidence: 99%
“…PA microdrops have been air-stripped by a coaxial nozzle into a polycation solution flowing in a multiloop chemical reactor for the preparation of spherical and monodispersed PEC capsules [7]. This encapsulation protocol preserved the high viability of the encapsulated recombinant Escherichia coli (E. coli) cells with overproduced ezymes from the group of Baeyer-Villiger monooxygenases (BVMOs) as well as their long-term storage and operational stability [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, Abril et al showed another CHMO immobilization example, but no information concerning its recycling was given [26]. Very recently, recombinant Escherichia coli whole-cells overexpressing cyclopentanone monooxygenase (CPMO) were encapsulated in polyelectrolyte complex capsules which rendered a biocatalyst more active and stable than the corresponding free cells [27]. In this study we explored the potential of several amino polyphosphazenes to covalently attach phenylacetone monooxygenase (PAMO) from Thermobifida fusca [28] and G6PDH.…”
Section: Introductionmentioning
confidence: 99%